Directive and Assertive Speech in Najwa Shihab's Interrogative Rhetoric: A Study by The Podcast “Mata Najwa” - Rifatul Hasanah; Ali Manshur (Jurnal Sastra Indonesia, 2026)
This study examines the use of directive and assertive speech in Najwa Shihab's interrogative rhetoric on the Mata Najwa podcast, employing the Critical Discourse Analysis (CDA) approach. This research departs from the view that journalistic questions are not neutral but function as a discursive strategy laden with power relations and ideologies. The method used is a descriptive qualitative method with a pragmatic theoretical framework (Searle's speech act) and Fairclough's three-dimensional CDA model, including text analysis, discursive practices, and social practices. The research data consists of Najwa Shihab's speech, which contains directive and assertive statements in the form of interrogative rhetoric, transcribed from Mata Najwa's podcast episodes. Data collection is conducted through listening, recording, and document study, while data analysis proceeds through the stages of identification, classification, pragmatic interpretation, and critical discourse analysis. The results of the study identified three main patterns of the use of speech in Najwa Shihab's interrogative rhetoric, namely: (1) indirect directive speech to direct the interpretation of the source, (2) explicit directive speech to control the focus and flow of argumentation, and (3) assertive speech in the form of interrogative to implicit insert ideological claims and assumptions. These three patterns systematically frame the speakers within the logic of public accountability, while simultaneously strengthening the media as a hegemonic actor in the production and control of discourse. From the perspective of Critical Discourse Analysis, the practice reproduces the ideology of state criticism, the supremacy of public rationality, and the demands of institutional responsibility. The novelty of this research lies in integrating directive and assertive speech analysis into the format of interrogative rhetoric in broadcast media, demonstrating that journalistic questions are not neutral but function as a discursive strategy to frame meaning, direct interpretation, and shape public awareness. Thus, the interrogative rhetoric in the Mata Najwa podcast is understood as a language practice that actively reproduces power relations and ideologies in the digital public space.